The effects of exercise-induced muscle damage on agility and sprint running performance - Highton, J. M.; Twist, C.; Eston, R. G. (Journal of Exercise Science & Fitness, 2009)
The purpose of this investigation was to assess the effects of exercise-induced muscle damage (EIMD) on agility and linear sprint running performance. Twelve healthy adults were randomly allocated to a treatment group (n = 7; age, 21 ± 1.2 years; height, 1.77 ± 0.11 m; body mass, 70.8 ± 8.2 kg) where they completed 100 plyo- metric jumps, or to a control group (n = 5; age, 24 ± 0.7 years; height, 1.77 ± 0.07 m; body mass, 69.2 ± 8.8 kg). Perceived muscle soreness, isokinetic peak torque of the knee extensors at 60 and 270 deg·s-1, sprint running time over 5 and 10 m, a timed agility test and ground contact time at the agility turn point were recorded at baseline and then 24, 48 and 168 hours following muscle-damaging exercise. Perceived muscle soreness was significantly increased (p < 0.05) and isokinetic peak torque at 60 and 270 deg·s-1 was significantly decreased (p < 0.05) at 24 and 48 hours in the treatment group following plyometric exercise. Significant increases (p < 0.05) were also observed for 5 m (6%) and 10 m (5%) sprint time, agility time (8%) and ground contact time at the agility turn point (21%), peaking at 48 hours in the treatment group. All variables remained unchanged in the control group (p > 0.05). These findings indicate that agility and sprint performance is reduced following EIMD, and provides further evidence that performance of activities requiring rapid generation of force is impaired following muscle-damaging exercise.